2000
DOI: 10.1191/096120300678828758
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to human myeloperoxidase in glomerular immune deposits of systemic lupus erythematosus

Abstract: Antibodies to human myeloperoxidase and cathepsin G have been detected in the serum of some patients with systemic lupus erythematosus. Therefore, the presence of antibodies to human myeloperoxidase and cathepsin G was examined in glomerular immune deposits. Glomerular basement membrane fragments were prepared from renal tissues obtained at autopsy from 19 patients with systemic lupus erythematosus. IgG was extracted from the glomerular basement membrane fragments and tested with sensitive immunoassays for ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…It has been reported that anti-MPO antibodies have been reported in an inconsistent manner in SLE patients, which has been ascribed to detection methodology. The same study, however, reported that anti-MPO is deposited in the kidney glomerular basement membrane, the first study to do so [ 153 ].…”
Section: Mpo Usefulness As a Biomarker In Disease Statesmentioning
confidence: 99%
“…It has been reported that anti-MPO antibodies have been reported in an inconsistent manner in SLE patients, which has been ascribed to detection methodology. The same study, however, reported that anti-MPO is deposited in the kidney glomerular basement membrane, the first study to do so [ 153 ].…”
Section: Mpo Usefulness As a Biomarker In Disease Statesmentioning
confidence: 99%
“…Lupus nephritis is characterized by glomerular immune deposition with the presence of immunoglobulins and complement components in kidney biopsy specimens. The etiology of this deposition is still unknown; however, antibodies specific to dsDNA, Sm, SSA, SSB, and C1q have been shown in glomerular despositions of proliferative Lupus nephritis [57][58][59] .…”
Section: Pathogenesis Of Lupus Nephritismentioning
confidence: 99%
“…In contrast to other autoimmune kidney diseases that are restricted to a specific autoAb (e.g., anti-collagen IV Abs in glomerular basement membrane), a vast array of autoAbs characterize LN patients with distinct subsets present in the kidney [58]. Indeed, the pioneering experiment conducted by Mannik et al from 23 post-mortem kidneys revealed the presence of a large panel of polyreactive Abs targeting dsDNA/chromatin/histone, Sm/RNP, SSA/B, C1q, and phospholipids [59]. Thanks to lupus-prone animal models and high-throughput technologies, the list of LN-associated Abs has been extended (Table 5), and this list included:…”
Section: Nephropathic Antibodies In Lnmentioning
confidence: 99%